Functional torque ratios and torque curve analysis of shoulder rotations in overhead athletes with and without impingement symptoms - Zanca, G. G.; Oliveira, A. B.; Saccol, M. F.; Ejnisman, B.; Mattiello-Rosa, S. M. (Journal of Sports Sciences, 2011)
In this study, we evaluated the peak torque, functional torque ratios, and torque curve profile of the shoulder rotators in overhead athletes with impingement symptoms so as to examine possible alterations in response to sports training and shoulder pain. Twenty-one overhead athletes with impingement symptoms were compared with 25 overhead athletes and 21 non-athletes, none of whom were symptomatic for impingement. The participants performed five maximal isokinetic concentric and eccentric contractions of medial and lateral shoulder rotations at 1.57 rad/s and 3.14 rad/s. Isokinetic peak torque was used to calculate the eccentric lateral rotation-to-concentric medial rotation and the eccentric medial rotation-to-concentric lateral rotation ratios. An analysis of the torque curve profiles was also carried out. The eccentric lateral rotation-to-concentric medial rotation torque ratio of asymptomatic athletes was lower than that of non-athletes at both test velocities. The concentric medial rotation isokinetic peak torque of the asymptomatic athletes, at 3.14 rad/s, was greater than that of the non-athletes, and the peak appeared to occur earlier in the movement for athletes than non-athletes. These findings suggest that there may be adaptations to shoulder function in response to throwing practice. The eccentric medial rotation-to-concentric lateral rotation torque ratio was altered neither by the practice of university-level overhead sports nor impingement symptoms.